The paradox of obesity with normal weight; a cross-sectional study - Lahav, Yair; Kfir, Aviv; Gepner, Yftach (Frontiers in Nutrition, 2023)
To evaluate the prevalence of excessive adiposity among normal-weight individuals, and their cardiometabolic risk.